The Colonial Laws of New York from the Year 1664 to the Revolution . . ., at 687 (1894) - (:unkn) unknown (General Publisher, 1664)
Prohibited a slave from possessing or using a gun, pistol, sword, club, or other kind of weapon unless in the presence and at the direction of their Master or Mistress.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES